School and electronic bullying among adolescents: Direct and indirect relationships with sadness, sleep, and suicide ideation. Issue 1 (1st November 2022) - Sutter, Claudia C.; Stickl Haugen, Jaimie; Campbell, Laurie O.; Tinstman Jones, Jessica L.
Abstract: Introduction: Bullying is an increasing concern for education, health, and policy. Adolescence is a particularly vulnerable period for the development of depressive symptoms and suicidality following exposure to bullying. However, limited research investigating the potential impact of depressive symptoms on the bullying‐suicide relationship exists. Methods: Using national data ( N  = 13, 677) from the most recent 2019 Youth Risk Behavior Survey, the aim of the present study was to examine the prevalence among adolescents' (school/electronic) bullying victimization, depressive symptoms (sadness; sleep), and suicide ideation as well as their associations including direct and indirect relationships including exploring differences by gender and race/ethnicity. Results: Descriptive results indicated an increase in the prevalence of adolescents being bullied (both on school property and electronically), experiencing feelings of sadness, and hopelessness as well as a decrease in getting more than 8 h of sleep between 2017 and 2019. In 2019, over one‐third of respondents felt sad or hopeless almost every day for 2 weeks or more in a row, which stopped them from doing some usual activities. Structural equation modeling indicated that (school/electronic) bullying was directly associated with feelings of sadness/hopelessness and suicide ideation, with sadness mediating the link between bullying and suicide ideation. Conclusion: Now more than ever, it is critical to promote the collaboration between educators, mental health specialists, policymakers, and researchers to develop and implement evidence‐based strategies and approaches to preventing and reducing both bullying victimization and the associated psychological distress and mental health outcomes.